Direct generation of optical vortex beams with tunable topological charges up to 18th using an axicon. (November 2021) - Li, Ke; Tang, Kaifei; Lin, Da; Wang, Jing; Li, Bingxuan; Liao, Wenbin; Lin, Zhanglang; Zhang, Ge
Highlight: A method for generation and tunability of optical vortex beams have been demonstrated both numerically and experimentally. The method by using an axicon to obtain annular pump beam is efficient and can be employing to other types of laser system. The optical vortex beams with high beam quality and high orders have been achieved. Abstract: The optical vortex beam carrying an orbital angular momentum is of great significance for many applications. Many approaches to generate optical vortex beams have been demonstrated, however they still suffer from some drawbacks such as low conversion efficiency, poor beam quality and so on. Thus, how to produce the high beam quality vortex beams with high topological charges is still a challenge for us. In this work, a convenient method for generation and tunability of Laguerre-gaussian (LG) vortex beams by using an axicon has been demonstrated. The high beam quality LG0, m vortex beams with tunable topological charges up to 18th order are achieved. An axicon combined with a focused lens can transform the Bessel beam into an annular beam efficiently, which can be employed to reshape the pump beam. An effective theoretical model has been present to predict the threshold pump power of each LG0, m vortex beam in this compact LD-end-pumped Nd:YVO4 laser.